THE URGENCY OF DEVELOPING STUDENT’S HABITS OF MIND IN HIGH SCHOOL BIOLOGY LEARNING IN BANDUNG - Bariroh, Ghurrotul; Rochintaniawati, Diana; Nuraeni, Eni; Nurjhani Kusumastuti, Mimin (BIOMA : Jurnal Ilmiah Biologi, 2024)
Habits of mind is one of the dimensions of long-term learning that allow productive actions to occur and can produce positive student character in solving problems in their lives. The importance of habits of mind is in contrast to the ability of habits of mind of students in one of the high schools in Bandung City which is still low. Based on this, the researcher aims to analyze the biology learning process carried out by teachers to further understand the factors that influence students' habits of mind. The method used in this research is quantitative descriptive. The sample was chosen using convenience sampling, so that 34 samples were obtained from class X students and biology teacher at one of the state high schools in Bandung City. The research results show that the low level of students' habits of mind is because teacher has not implemented how to develop students' habits of mind in classroom learning. Differentiated learning, student centers, reflection activities, and learning independence in using resources are the next researchers' recommendations for interventions to improve students' habits of mind.